Systems-thinking skills exhibited by UITM Sarawak diploma students in solving problems / Foo Kien Kheng … [et al.] - Foo, Kien Kheng; Liew, Chin Ying; Lee, Elinda Ai Lim; Goh, Kelvin Tee Hiong (2006)
This study examines the conceptual and theoretical basis for developing a framework to measure systems-thinking skills and subsequently designs scoring rubrics to measure the performance level of the respondents’ problem solving and systems thinking. It is hypothesized that systems thinking can play a leading role by facilitating the attainment of important problem-solving skills. As part of the initial effort to determine if there is any basis for saying so, this exploratory study seeks to investigate whether an association exists between problem-solving and systems-thinking skills. It employed the survey methodology to gather data through a paper-and-pencil test and questionnaire. Four performance tasks were constructed to measure these skills. Following that, two scoring rubrics were created based on two pre-determined frameworks. Findings indicated that the general population performed poorly for problem solving and systems thinking. The mean score for systems thinking was even lower than that of problem solving. These skills were also analyzed according to three selected demographic characteristics. It was found that problem solving was not affected by gender and Gugusan where as CGPA did show dependency.